Empowering the Giri Muda Farmers Group through Biochar Production Training from Agricultural Waste in Ponjong, Gunungkidul - Mohammad Prasanto Bimantio; Amir Noviyanto; Galang Indra Jaya (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: The agricultural areas of Ponjong, Gunungkidul, are dominated by marginal drylands with low soil fertility and organic matter content. Farmers often rely on chemical fertilizers and open burning of crop residues, leading to soil degradation and environmental pollution. Biochar technology offers an eco-friendly solution to improve soil health and reduce waste.Aims: This study aims to strengthen the capacity of the Giri Muda Farmers Group in producing and applying biochar derived from agricultural waste and promoting sustainable soil management practices through participatory technology transfer.Methods: The program was implemented through participatory stages including preparation, socialization, training, demonstration, and field application. The rotary pyrolysis unit was introduced for efficient biochar production using rice straw and maize stalks as feedstock. Evaluation was conducted using pre- and post-tests, observation, and interviews.Results: Farmers demonstrated a 38% improvement in knowledge scores, and 100% of participants were able to operate the pyrolysis equipment independently. Field trials showed improved soil aggregation, higher moisture retention, and more vigorous maize seedling growth on biochar-amended plots. The farmers also committed to continuing biochar production collectively.Conclusion: The community service program successfully transferred appropriate pyrolysis technology to local farmers, improving soil quality, resource efficiency, and community empowerment. The initiative demonstrates that biochar production from agricultural waste can simultaneously address environmental issues and strengthen rural livelihoods.